2020
DOI: 10.1186/s12887-020-02171-0
|View full text |Cite
|
Sign up to set email alerts
|

Tübingen hip flexion splints for developmental dysplasia of the hip in infants aged 0–6 months

Abstract: Background: Developmental dysplasia of the hip (DDH) is a common disorder in infants. The present study aimed to evaluate the efficacy and safety of the Tübingen hip flexion splints in treating DDH in infants aged 0-6 months. Methods: This is a retrospective study analyzing 259 hips in 195 infants with DDH of Graf type IIc or worse classifications treated between January 2015 and December 2017. Patients were followed up for at least 6 months. Avascular necrosis of the femoral head was diagnosed using plain rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 20 publications
(23 reference statements)
2
12
0
2
Order By: Relevance
“…Following screening on the pre-specified criteria, including full text review of retained abstracts, eight articles in English and one in German were included in our analysis. 13 , 14 , 19 - 25 Two of these articles, by Kubo et al 13 , 20 used the same study group with outcomes measured at the mid-term and end-point of the period of follow-up. The flow diagram of study selection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Following screening on the pre-specified criteria, including full text review of retained abstracts, eight articles in English and one in German were included in our analysis. 13 , 14 , 19 - 25 Two of these articles, by Kubo et al 13 , 20 used the same study group with outcomes measured at the mid-term and end-point of the period of follow-up. The flow diagram of study selection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…26 The THFS has a similar success rate than the PH (84% to 99%) 27 , 28 but with a lower incidence of AVN. 5 , 14 Treatment failure with the PH may be due to the fact that it can only maintain the hip in 80° to 90° of abduction by gravity. 8 Moreover, clinical outcomes will be influenced by the use of the PH, namely if it is worn appropriately and sufficiently.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations